2012
DOI: 10.1111/j.1447-0594.2012.00923.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise and tea catechins on muscle mass, strength and walking ability in community‐dwelling elderly Japanese sarcopenic women: A randomized controlled trial

Abstract: The combination of exercise and tea catechin supplementation had a beneficial effect on physical function measured by walking ability and muscle mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
174
0
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(187 citation statements)
references
References 31 publications
(65 reference statements)
3
174
0
10
Order By: Relevance
“…The subjects were recruited using the following various methods: a local press advertisement [14], flyers [18], invitation letters [15, 16], as well as in-person explanations in local field centers [10, 11, 13], residential care facilities [17] and university ambulatory sections [12]. These subjects were general people [10, 12, 14, 18] but also included partially a special population, for instance with sarcopenia [15, 16] and with mobility disability [11, 13, 17].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The subjects were recruited using the following various methods: a local press advertisement [14], flyers [18], invitation letters [15, 16], as well as in-person explanations in local field centers [10, 11, 13], residential care facilities [17] and university ambulatory sections [12]. These subjects were general people [10, 12, 14, 18] but also included partially a special population, for instance with sarcopenia [15, 16] and with mobility disability [11, 13, 17].…”
Section: Resultsmentioning
confidence: 99%
“…These subjects were general people [10, 12, 14, 18] but also included partially a special population, for instance with sarcopenia [15, 16] and with mobility disability [11, 13, 17]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies demonstrated that dietary supplementation with amino acids (7) or tea catechins (8) combined with low-intensity regular exercise improved physical performance, muscle mass, and strength in older adults.…”
mentioning
confidence: 99%
“…However, TUG, which is a physiological index of skeletal muscle function, was improved by catechin ingestion alone (p<0.05). Recently, catechin with exercise training was reported to have a beneficial effect on skeletal muscle function measured by TUG and skeletal muscle mass [29]. However, this is the first study showing that catechin-ingestion without exercise training could improve walking ability measured by TUG in healthy elderly women.…”
Section: Effects Of Catechin-ingestion On Skeletal Muscle Mass and Fumentioning
confidence: 75%